SEBERAPA BESAR PENGARUH TEKNOLOGI JIKA SUDAH BERLEBIHAN - Rifanny Balqis, Rifanny Balqis; Mahammad Irwan Padli Nasution (Kohesi: Jurnal Sains dan Teknologi, 2024)
The influence of technology on current human life is extremely significant, yet excessive usage can result in negative impacts.In this context, communication technology, social media, and digital devices often take center stage.Excessive use can lead to mental health disorders, such as anxiety and depression, as well as impact social interactions and productivity. This research aims to explore various aspects of the negative impacts of excessive technology use, as well as strategies for mitigating these effects, such as implementing healthy screen time and promoting digital awareness.By understanding this influence, individuals and society are expected to take wiser steps in utilizing technology to enhance their quality of life. Please rewrite this text in a smooth manner by adding two line breaks where necessary. Keywords: Technology, negative influences,excessive use, mental health, social interaction, productivity, digital awareness